DETERMINANTS OF NET INTEREST MARGIN OF LISTED COMMERCIAL BANKS IN INDONESIA - Megawaty, Linda; Ugut, Gracia S (Universitas Muhammadiyah Tapanuli Selatan, 2022)
The purpose of this study is to identify the determinants of Net Interest MarginÂ in listed commercial banks in Indonesia, particularly the banks which are under the category of BUKU III and BUKU IV. The study uses a set of independent variables which are classified to bank-specific variables (asset size, capital adequacy ratio, asset quality, liquidity, deposits, assets management, operating efficiency, leverage) and macro-economic variables (exchange rate, inflation rate, interest rate, economic growth). The methodology used in this research is a data panel regression approach where common effect, fixed effect and random effect model are built using five-year-secondary data for period of 2015-2019. The sampling data are taken from 21 listed commercial banks in Indonesia categorized under BUKU III and BUKU IV. The result of this study indicates that capital adequacy, asset quality, deposits, asset management, and exchange rate have significant impacts on NIM.